2018
DOI: 10.1016/j.jpha.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Unusual retention behavior of omeprazole and its chiral impurities B and E on the amylose tris (3-chloro-5-methylphenylcarbamate) chiral stationary phase in polar organic mode

Abstract: Recent reports have demonstrated that the new commercially available immobilized-type chiral stationary phases (CSPs) containing amylose tris(3-chloro-5-methylphenylcarbamate) (ACMPC) as a selector exhibit not only an exceptionally high enantioselectivity in high-performance liquid chromatography (HPLC) but they are also applicable to a wide range of chiral analytes. Herein, we report the results obtained in the HPLC analysis of omeprazole and its impurities B and E on the ACMPC-based Chiralpak IG-3 CSP (CSP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In fact, in aprotic polar organic mode, the first enantiomer of OXFZ was not eluted from the IG-3 column after 50 min. Such uncommon retentive behavior has already been observed on the same CSP using omeprazole as a selectand [4].…”
Section: Analytical Hplc Enantioseparation In Polar Organic Conditionssupporting
confidence: 63%
See 2 more Smart Citations
“…In fact, in aprotic polar organic mode, the first enantiomer of OXFZ was not eluted from the IG-3 column after 50 min. Such uncommon retentive behavior has already been observed on the same CSP using omeprazole as a selectand [4].…”
Section: Analytical Hplc Enantioseparation In Polar Organic Conditionssupporting
confidence: 63%
“…It has been prepared by immobilizing amylose tris(3‐chloro‐5‐methylphenylcarbamate) (ACMPC) onto 3 μm particles of silica. Previous works have demonstrated that ACMPC‐based CSPs can be successfully used for the direct resolution of different biologically active compounds in combination with typical normal phase and polar organic mobile phases . However, its use for HPLC enantioseparations with aqueous eluents has not been evaluated yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was explained as being caused by the non‐stereoselective hydrogen bondings between analytes and the CSP, which can be minimized in this way. The influence of temperature was also evaluated, while the enantioseparations of OME and Impurity‐E were found to be unusually entropically – driven whereas the resolution of Impurity‐B was an enthalpically – driven process [77].…”
Section: Hplc Methodsmentioning
confidence: 99%
“…In the Chiralpak IG-3 CSP, the amylose tris(3-chloro-5-methylphenylcarbamate) (ACMPC) polymeric selector was immobilized onto 3-μm silica particles [ 8 ]. Recent studies showed that meta-substituted ACMPC-based CSPs can be successfully applied to develop enantioselective HPLC protocols useful for the resolution of biologically active chiral compounds [ [9] , [10] , [11] ] in both normal-phase and aqueous modes [ 12 , 13 ]. In addition, the ACMPC selector was also shown to be effective for the simultaneous separation of structurally related chiral analytes [ 8 , [12] , [13] , [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%